Fesach Agada ("Paschal Legend") and its Significance for Kartvelology - Reuven Enoch (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
For hundreds of years oral translations of the Scriptures and prayers were created in the vernacular of the Georgian Hebrews. These translations were handed down oraly from generation ot generation, coming down ot us. Text of the Fesach Agada - highly significant for Hebrews is among them. It tells about the miraculous deliverance of the Hebrews from Egypt and is read in the first night of the festival Fesach (Passover) - dedicated to this event (in the diaspora it is read on the second night as well), at a specially arranged festive meeting. As a rule, Agada was read in the holy language, but under conditions of millennial sojourn of Hebrews in Georgia a large part of Hebrews forgot Hebrew, and the text was incomprehensible to them. Therefore, the spiritual preceptors of Georgian Hebrews apparently decided to translate it into Georgian. Among Georgian Hebrews there presumably existed a ban on writing religious books in Georgian. Hence the translation was made orally. The Agada text acquires special significance both for research into the translations of the Scripture and prayers and the languages and speech of the Hebrews, and for Georgian philology, for this is actually a living text coming down to us from the depth of centuries; it provides rich evidence for both the study of the history of the Georgian schools of translation and (what is more) for research into the history and historical dialectology of the Georgian language, inasmuch as through this text we can trace the process, the dynamics of changes, language layers (e.g. declension of nouns, the relationship of the modifier and the modified, the article, syntactic peculiarities, etc. Especially interesting si the rich vocabulary of the present translation.